Mekanisme Pertahan Diri Trauma Korban Pelecehan Seksual Tokoh Dalam Film “Hope” : Studi Konseling Psikoanalisis - Adinda Zahro Melati; Imalatul Khairat; Lutfi Aprilia; Farhan Alfa Rizki (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study explores the traumatic experiences experienced by Sowon, a girl who is a victim of sexual abuse in the film Hope. The film depicts her emotional and psychological journey after experiencing violence, as well as the impacts that arise in her life. Using a psychoanalytic counseling approach, this study identifies various self-defense mechanisms that Sowon uses in dealing with trauma. Various negative emotions such as pain, fear, and loss of control become part of her struggle in facing the bitter reality. The findings show that Sowon develops self-defense mechanisms such as denial, diversion, and regression as a way to survive in an unstable psychological condition. In addition, support from parents and counselors plays an important role in helping her build more effective coping strategies. This study aims to provide a deeper understanding of the psychological impact of sexual violence on children, as well as emphasize the importance of appropriate counseling interventions in the victim's recovery process. Thus, the results of this study are expected to contribute to the development of more effective counseling theories and practices for victims of sexual abuse.